INTEGRATING INNOVATIVE METHODS OF TEACHING AND LEARNING ELECTRONICS IN TECHNICAL VOCATIONAL EDUCATION (TVE) FOR SUSTAINABLE DEVELOPMENT IN IMO STATE (NAU Journal of Technology and Vocational Education, 2025)
The study investigated the integration of innovative methods of teaching and learning Electronics in Technical Vocational Education for sustainable development in Imo state. Descriptive survey design was adopted for the study. The population of study comprised of 35 respondents.  Intact class was and census sampling were used because of the smallest of the numbers. A 20-item questionnaire tagged “Innovative Method of Teaching and Learning Electronics (IMTLE)” was used for data collection, which was validated by three experts and trial tested outside the area of study.   The questionnaire items were generated from the review of the related literature. All the 35 copies of the questionnaire administered were returned. Mean and standard deviation were used to answer the research questions while T-test statistic was used to analyze the hypothesis. Mean of 3.50 were considered needed. The reliability coefficient was 0.81, established using Cronbach alpha to analyze the hypothesis. The result of the study revealed that 10 innovative methods were needed to be integrated in the teaching and learning electronics. The results also showed that electronics lecturers/educators were not sufficiently integrating the innovative methods in teaching and learning. The researcher among others recommends that electronics lecturers/educators should be encouraged to update their knowledge in the use of innovative teaching and learning by attending conferences and workshops, in service training and other continuous education opportunities.
Keywords: Technical Vocational Education; Sustainable Development; Electronics; Innovation